Platelet-rich plasma as a new treatment method in orthopedics - Aleksandra Janocha; Aneta Jerzak; Anna Hitnarowicz; Bożena Kmak; Anna Szot; Agnieszka Pociecha (Kazimierz Wielki University, 2024)
Introduction and purpose Platelet-rich plasma (PRP) therapy represents a technology designed to enhance tissue repair by locally administering one's own bioactive agents, aiming to influence physiological processes like inflammation, angiogenesis, and extracellular matrix synthesis. Recently, the use of PRP therapy has become a subject of discussion in the orthopedic field. This review comprehensively examines the mechanisms, contemporary applications, clinical evidence, safety aspects, and potential future advancements of PRP in orthopedic treatment. Research has documented the efficacy of PRP injections in achieving full regeneration and enabling a comeback to competitive sports. PRP injections could serve as a viable alternative treatment for individuals with lateral tendonitis when compared to surgery. Further research investigating the impact of PRP on the bone healing process following a fracture is warranted. Materials and methods The methodology for conducting literature search involved utilizing medical subject headings terms to explore PubMed. Search terms included: "plasma-rich therapy", "tendinopathy",  "injury" " articular cartilage ", "bone fracture " Conclusions Research at different evidence levels has shown that PRP is safe and has beneficial effects in above uses. Due to the autologous nature of the therapy, side effects are minimal. In the majority of cases, PRP therapy alleviates pain sensations in both short- and long-term observations, facilitating a faster return to daily functionality. However, additional randomized, controlled clinical trials are anticipated to be conducted in the future. Progressing further necessitates the standardization of methods for preparing plasma and procedures for its application.